Re-Thinking Housing: From Physical Manifestation of Colonial Planning Policy to Community-Focused Networks - McCartney, Shelagh (Urban Planning, 2016)
Current housing systems and policies for First Nations communities in Canada produce a physical manifestation of ongoing colonialism: the house. Examinations of the physical community and house yield an understanding of deeply systematized imperial struggles between Indigenous communities and planning as a discipline. Indigenous families are in crisis as the housing system and Federal planning policies have not allowed for the provision of adequate nor appropriate homes. The recent independent Truth and Reconciliation Commission has begun a civic discussion, accompanied by a new federal government looking to begin a new relationship with Indigenous peoples—here we explore how planning can be a leader in this shift. The ‘contact zone’ is used as an operational lens to examine the ways discourse is used to shape the existing housing system. An interdisciplinary and global approach informs interventions in the existing housing system and policies, creating a community-driven model, and uncovering a reimagined role for the planner.